PENGARUH AIR REBUSAN JAHE MERAH (Zingiber officinale Var. Rubrum) TERHADAP KADAR GULA DARAH PASIEN DIABETES MELITUS DI DESA MEKARJAYA - Fitrianti Dewi; Selvy Afrioza (Nusantara Hasana Berdikari, 2022)
Changes in people's lifestyles led to an increase in diabetes mellitus in several areas, including Mekarjaya Village Sepatan Subdistrict with survey data that 78 people were identified as having diabetes mellitus. It is affected by high blood sugar levels, obesity and a history of heredity. So it is necessary to do treatment to control and prevent the occurrence of long-term complications with nonpharmacological treatment one of which is red ginger stew water. The purpose of the study was to find out the effect of red ginger boiled water (Zingiber officinale var.rubrum) on the blood sugar levels of patients with diabetes mellitus mekarjaya village. The research design used aquantitative method Quasi Experiment with a pretest-intervention-posttest design. The population is 78 people and the sample is 60 people with purposive sampling technique. The research instrument uses an observation sheet and the analytical test used is theNormality Kolmogorov- Smirnovtest, Wilcoxon Signed Rank Test and statistical tests Mann-Whitney. The results of the study obtained blood sugar levels before giving red ginger stew water 261.40 mg / dl, while after 208.97 mg / dl. The results of the Wilcoxon Signed Rank Test and Mann-Whitney analysis test obtained a significant value p < α = 0.05 means that there is an effect of red ginger boiled water on the reduction of blood sugar levels in patients with diabetes mellitus in Mekarjaya Village. The conclusion is that there is an influence on blood sugar levels before and after the administration of red ginger in patients with diabetes mellitus.